Study on the Influence of Failure Learning on the Performance of Start-ups - Rastogi, Amenawo (International Journal of Accounting and Financial Reporting, 2023)
Many entrepreneurs have failed at one time or another. Entrepreneurs need to reflect on the failure and summarize the experience in time, so as to accumulate useful information for the second venture. Based on entrepreneurial learning theory and cognitive dissonance theory, this paper takes 258 entrepreneurial teams in the Yangtze River Delta as research objects, explores the impact of entrepreneurial failure learning on entrepreneurial performance, and verifies the moderating effects of ascending counterfactual thinking and descending counterfactual thinking. The results show that entrepreneurial failure learning has a significant positive impact on the performance of new ventures. Upward counterfactual thinking positively moderates the relationship between failure learning and entrepreneurial performance, but downward counterfactual thinking has no significant moderating effect between failure learning and entrepreneurial performance. After the downward counterfactual thinking is added, the triple interaction effect is significant, that is, the upward counterfactual thinking and the downward counterfactual thinking jointly positively regulate the relationship between failure learning and entrepreneurial performance.